Determinants of the use of nutritional information among grocery shoppers in Penang - Khaminiswari Vijayakumar; Jacqueline Liza Fernandez (Penerbit Universiti Kebangsaan Malaysia, 2018)
The consumption of processed food products is common today. The Ministry of Health and consumer associations in Malaysia are actively promoting the use of nutritional information displayed on food labels to inculcate healthy eating habits among Malaysians. This study investigates the use of nutritional information among grocery shoppers in one particular state in Malaysia, i.e. Penang. A survey involving 404 respondents was carried out in Penang for the purpose of this study. A logit model was estimated based on the survey data to examine the factors that affect the use of nutritional information by shoppers. The results indicate that gender, age, education, time spent on grocery shopping, price/cost considerations, smoking status and health status are significantly related to the use of nutritional information when purchasing processed food products. The findings of this study are used to propose measures that can be taken to motivate more consumers to use nutritional information when purchasing processed food products. The steps taken should be targeted at the following groups of individuals: men, older and less educated shoppers, speedy shoppers, price-sensitive buyers, smokers and individuals with health problems. Strategies such as introducing pricing policies and self-checkout stations that saves time for shoppers should be considered to increase the likelihood of using nutritional information among grocery shoppers.